1999
DOI: 10.1111/j.1151-2916.1999.tb02246.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ion‐Beam Irradiation Effects in X2YO4 Compounds

Abstract: O 4 ), and phenakite structures have been investigated using in situ and high-resolution transmission electron microscopy (HRTEM) over a wide temperature range (20-873 K). At low temperatures (<200 K), the olivine and phenakite are susceptible to radiation-induced amorphization with a critical amorphization dose of 0.2-0.5 displacement per atom (dpa). The critical amorphization dose increases with increasing irradiation temperature at varying rates for the various phases, resulting in a distinct critical amorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…No detectable radiation damage in the apatite suggests a higher resistance against amorphization due to more rapid annealing of the radiation damage. Irradiation experiments with 1.5 MeV Kr + ions conducted by Wang et al (1994) under comparable conditions to the experiments of Wang et al (1999) showed that the critical, upper temperature of amorphization of Fa 12 olivine and fluorapatite are very similar. Increasing Fe contents of olivine shifts this temperature to higher values (i.e., the structure becomes more vulnerable), and therefore, the observed difference between the two phases in our sample is probably due to the olivine?…”
Section: Space Weathering Of Phosphates and Troilite In Ra-qd02-0115mentioning
confidence: 80%
See 3 more Smart Citations
“…No detectable radiation damage in the apatite suggests a higher resistance against amorphization due to more rapid annealing of the radiation damage. Irradiation experiments with 1.5 MeV Kr + ions conducted by Wang et al (1994) under comparable conditions to the experiments of Wang et al (1999) showed that the critical, upper temperature of amorphization of Fa 12 olivine and fluorapatite are very similar. Increasing Fe contents of olivine shifts this temperature to higher values (i.e., the structure becomes more vulnerable), and therefore, the observed difference between the two phases in our sample is probably due to the olivine?…”
Section: Space Weathering Of Phosphates and Troilite In Ra-qd02-0115mentioning
confidence: 80%
“…The implantation of energetic particles into crystalline structures causes displacements of ions from structural lattice sites into interstitial positions, the sum of many such displacements eventually leads to amorphization. In situ irradiation experiments by Wang et al (1999) using 1.5 MeV Kr + ions directed at approximately 300 nm thick foils of Fa 12 olivine showed that the disordering of the structure starts with the cations being preferentially knocked into interstitial positions, while the anion sublattice remains intact for a longer time at a given ion flux. Similar experiments by Christoffersen and confirmed that amorphization progresses by the formation of amorphous domains within a residual crystalline matrix that shows no crystallographic misorientations.…”
Section: Space Weathering Of Olivine In Ra-qd02-0115mentioning
confidence: 99%
See 2 more Smart Citations
“…The average number ofatomic displacement produced per He implantation event can be evaluated with the Monte Carlo computer code TRIM (TRansport of Ions in Matter; Ziegler et al, 1996). Assuming a displacement energy of25 eV for all species (Wang et al, 1999), there were~40 (4 keV), 70 (10 keV) and 120 (50 keY) atomic displacements per He implantation. The completely amorphous state is the consequence ofaccumulation and overlap ofthe individual events.…”
Section: Chemical Evolutionmentioning
confidence: 99%